Rheological and Technological Aspects of UV Curing Thick Polymer Layers with Fiber Reinforcement (Annual Transactions of the Nordic Rheology Society, 2025)
UV curing allows energy-efficient and fast resin solidification for many different applications. By combining suitable photoinitiators and light-emitting diode (LED) light sources, cure depths of more than 1 mm have become available, which makes UV curing also a promising candidate for the development of innovative manufacturing technologies, including fiber-reinforced polymers (FRP). This contribution suggests experimental methods that help to understand the interaction between process parameters, curing behavior, and resulting material properties of a novel UV resin. UV-rheology is used to replicate close to reality process conditions during curing as well as to analyze the underlying phenomena, including the mechanical and volumetric material behavior. When investigating thick polymer layers, opposing effects such as heat accumulation within the resin volume and limited penetration depth of the UV light need to be taken into account. Both effects will have an influence on the reaction rate and at the same time affect the optical properties of the resin. By evaluating UV-rheological experiments in conjunction with additional experimental data obtained in UV-DSC, a holistic understanding of the governing phenomena during UV curing of thick reinforced and unreinforced polymers becomes possible.